Assessment of prevalence of protein energy malnutrition in under 5 year children in an urban slum of Mumbai, India and to study associated factors - Tiwari, Shraddha R.; Bandi, Janardhan R.; Awasthi, Sukarn R.; Sharma, Aakash K. (International Journal Of Community Medicine And Public Health, 2017)
Background: In urban slums, several socio-demographic factors contribute for the occurrence of protein energy malnutrition (PEM) in under-five year children, this study aims at Assessment of prevalence of protein energy malnutrition in under-5 year children in an urban slum of Mumbai and to study associated factors. Methods: A cross-sectional study was conducted in Urban Slum which is a field practice area of institition.Under-5 children were included in the study and information was gathered by interviewing mother/guardian and recording anthropometric measurement of the child. Data was analysed with SPSS v.16 with suitable tests. Result: Prevalence of PEM was found 56%, more per cent of PEM was found in 13-24 month age 64 (66.7%), 120 (54.1%) boys, 122 (55%) non-nuclear family dwellers, in 126 (56.8%) children whose mothers got married<18 years age. About 116 (52.3%) children of illiterate mothers, 158(71.2%) children of birth order >2, 198(89.2%) children who were not given colostrum and 168 (75.7%) who were not given exclusive breast feeding, in 152(68.5%) children with incomplete immunisation, 122 (55%) children with more than 3 episodes of ARI, 142(64%) with >3 episodes of Diarrhoea. 86 (82.7%) children with PEM belonged to Class V, (B.G Prasad classification), statistically significant association of PEM was found with the factors age of child, mother’s education, birth order, immunisation status, mother’s age at marriage, exclusive breast feeding, history of acute respiratory infection (ARI) and diarrhoea, and socio-economic status. Conclusion: Study has found certain socio-demographic factors like age, gender and birth order of child, type of family, age of mother during marriage and her literacy level, giving colostrum, exclusive breast feeding, immunisation and frequency of ARI and diarrhoea associated with PEM.